Nutritional Status and Its Association With Radiation-Induced Oral Mucositis in Patients With Nasopharyngeal Carcinoma During Radiotherapy: A Prospective Study - Shu, Zekai; Zeng, Ziyi; Yu, Bingqi; Huang, Shuang; Hua, Yonghong; Jin, Ting; Tao, Changjuan; Wang, Lei; Cao, Caineng; Xu, Zumin; Jin, Qifeng; Jiang, Feng; et al. (Frontiers in Oncology, 2020)
Background & Aims: Malnutrition is a concern in patients with nasopharyngeal carcinoma (NPC) during chemoradiotherapy (CRT)/radiotherapy (RT), which is considered to be related with radiation–induced oral mucositis (ROM). The study aimed to evaluate the nutritional status of NPC patients during RT and investigate its association with ROM. Methods: A prospective study was conducted in NPC patients. Patients were divided into three subgroups (mild, moderate, and severe groups) based on the duration of severe ROM (≥ grade 3). Body weight, body mass index (BMI), albumin, prealbumin, NRS2002, and ROM grade were assessed on a weekly basis before and during CRT/RT. The statistical analysis was performed in the overall group and between three subgroups. Results: A total of 176 patients were included. In the overall group, body weight and BMI kept decreasing since week 1 of RT, and NRS2002 score and ROM grade increased (p < 0.001). NRS2002 score and prealbumin levels were significantly different between each subgroup (p ≤ 0.046). Significant differences were observed in the proportion of patients receiving enteral nutrition, duration of parenteral nutrition, and total calories provided by nutritional support among three subgroups (p = 0.045–0.001). Conclusions: Malnutrition occurred early in NPC patients and worsened continuously during RT. ROM was strongly associated with nutritional status. Nutritional support should be provided at the start of RT, especially in patients at high-risk of severe ROM.